2009
DOI: 10.1111/j.1462-2920.2008.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial eukaryotes in the hypersaline anoxic L'Atalante deep‐sea basin

Abstract: The frontiers of eukaryote life in nature are still unidentified. In this study, we analysed protistan communities in the hypersaline (up to 365 g l(-1) NaCl) anoxic L'Atalante deep-sea basin located in the eastern Mediterranean Sea. Targeting 18S ribosomal RNA retrieved from the basin's lower halocline (3501 m depth) we detected 279 protistan sequences that grouped into 42 unique phylotypes (99% sequence similarity). Statistical analyses revealed that these phylotypes account only for a proportion of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(180 citation statements)
references
References 130 publications
(212 reference statements)
2
176
2
Order By: Relevance
“…Euglenozoan, jakobid, rhizarian and choanoflagellate signatures were only detected in the UI, indicating a decrease in diversity in the anoxic and more hypersaline layer. Other studies have found ciliates to dominate the eukaryotic microbial community in upper DHAB haloclines (Alexander et al, 2009;Edgcomb et al, 2009), but we observed a decrease in the relative abundance of ciliate rRNA as environmental conditions become more challenging in the LI, where Fungi appear equally abundant.…”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation
“…Euglenozoan, jakobid, rhizarian and choanoflagellate signatures were only detected in the UI, indicating a decrease in diversity in the anoxic and more hypersaline layer. Other studies have found ciliates to dominate the eukaryotic microbial community in upper DHAB haloclines (Alexander et al, 2009;Edgcomb et al, 2009), but we observed a decrease in the relative abundance of ciliate rRNA as environmental conditions become more challenging in the LI, where Fungi appear equally abundant.…”
Section: Resultscontrasting
confidence: 47%
“…Based on SSU rRNA gene transcripts recovered within our metatranscriptome libraries, the eukaryotic community appears to be dominated by ciliates and dinoflagellates in the UI, and by ciliates and fungi in the LI (Figure 2). Previous studies of DHABs, including Thetis, based on SSU rRNA and microscopic observations have detected heterotrophic protists (particularly ciliates, dinoflagellates and fungi) in up to 36% salinity (see, for example, Alexander et al, 2009;Edgcomb et al, 2009;Stock et al, 2012). Phagotrophic protists are known to be successful along pelagic oxyclines where prokaryotes are abundant (see, for example, Behnke et al, 2006;Edgcomb et al, 2011a) and hence it follows that they are also successful within these haloclines.…”
Section: Eukaryotic Signaturesmentioning
confidence: 99%
“…Indeed, microbial life from all three domains has been shown to occur in such aquatic systems (e.g. van der Wielen et al 2005;Daffonchio et al 2006;Alexander et al 2009;Borin et al 2009;Yakimov et al 2007a). While new cell morphologies and ecophysiological traits have been assigned to some of these microorganisms, only recently a more specific picture of the metabolic activities of DHAB microorganisms has started to emerge, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…6. Abbreviations: CI to CIV, respiratory complexes I to IV; UQ, ubiquinone; RQ, rhodoquinone; C, cytochrome c; A, ATPase; FRD, fumarate reductase; SQR, sulfide:quinone oxidoreductase; ST, sulfur transferase; SD, sulfur dioxygenase; [2B], acetate:succinate CoA-transferase (subfamily 1B); [3], succinyl-CoA synthetase; [5], malic enzyme; [6], pyruvate dehydrogenase complex; [8], fumarase; [9], pyruvate kinase; [10], phosphoenolpyruvate carboxykinase (ATP dependent); [11], malate dehydrogenase; [14], methylmalonyl-CoA mutase; [15], methylmalonyl-CoA epimerase; [16], propionyl-CoA carboxylase; [18], alanine aminotransferase; [19], aspartate aminotransferase; [20], alanopine dehydrogenase; [26] A strictly anoxic animal among the loriciferans. All animals with anaerobic metabolism discussed above do encounter oxygen permanently or from time to time.…”
Section: Figmentioning
confidence: 99%